The amount and detection method of styrene in foods: A systematic review and meta-analysis - Parisa Sadighara; Nader Akbari; Parisa Mostashari; Najmeh Yazdanfar; Samira Shokri (Food Chemistry: X, 2022)
The ingredients in food packaging migrate to the food inside. One of the most common compounds used for packaging of food is polystyrene. This systematic review aimed to investigate the level of styrene’s pollution in food packed with polystyrene. The original articles include keywords styrene, polystyrene, food, contamination, pollution, “food packaging” were searched in Web of science, Medline, Scopus, and Science Direct. A total of 227 studies were achieved. The articles that did not meet the inclusion criteria were excluded with the initial evaluation. The quality assessment was conducted for full paper and finally data were extracted from 8 selected articles. Mata analysis, meta-regression, subgroup analysis, and publication bias was also conducted with comprehensive meta-analysis (CMA) software. Most of the examined samples were dairy products. The amount of fat in dairy products is an important factor in increasing the migration of styrene. The shelf life of product also had effect on migration of styrene. The overall average was estimated as 91.53 ± 26.18 µg/kg in food matrix. This amount is less than the permissible level. The results of meta regression showed that the type of food affects the pooled mean of styrene in the food. There was no publication bias for the selected articles.